In Latin America: Power and non-power of technologies - Torres Acuña, Luis (1988)
We will begin this text with a categorical and central statement that will serve as the basis for the present essay: posing the political question in relation to the so-called New Technologies implies problematizing the most relevant and substantial aspects of them, in terms of the importance they have for our Latin American society. In short, the so-called New Technologies do not constitute strange entities and alien to the social, which descend from somewhere and "permeate" social life. Rather they are subject, in some way, to a complex form of socio-historical causal determinism, which founds and explains them.